THE INFLUENCE OF EXPECTATION OF RETURN AND PERCEPTION OF RISK TOWARDS THE INTEREST OF INVESTING ON REGISTERED STUDENT INVESTORS IN THE INDONESIA STOCK EXCHANGE INVESTMENT GALLERY AT STATE UNIVERSITY OF JAKARTA : PENGARUH EKSPEKTASI RETURN DAN PERSEPSI RISIKO TERHADAP MINAT INVESTASI INVESTOR MAHASISWA YANG TERDAFTAR DI GALERI INVESTASI BURSA EFEK INDONESIA UNIVERSITAS NEGERI JAKARTA - Izzati Fareva; Sri Zulaihati; Ati Sumiati (Yayasan Education and Social Center, 2021)
This research aims to know the influence of expectation of return and perception of risk towards the interest of investing on registered students investors in the Indonesia Stock Exchange Investment Gallery at Universitas Negeri Jakarta. A survey with a quantitative approach is the method that this study used. The accessible population in this study is 100 students and using a sample of 78 students. The data collection tool used was a questionnaire. Through multiple linear regression analysis, the study found that expectation of return has a positive and significant effect on interest of investing, perception of risk has a negative and significant effect on interest of investing, and simultanously they have a significant effect on the interest of interest investing. The conclusion that can be drawn in this study is that the expectation of return and perception of risk affect the interest of investing